Features of sacral alar fatigue fractures in adolescent athletes with overuse - Masaki Tatsumura (Nature Portfolio, 2021)
Abstract Three types of sacral alar fatigue fractures are elderly, postnatal, and sport-related. They are most prevalent in athletes during adulthood; there are few reports of sacral alar fatigue fractures in young athletes. The purpose of this study was to analyze sacral alar fatigue fractures in adolescent athletes. Of the 920 patients hospitalized with low back pain, 13 were diagnosed with sacral alar fatigue fractures with magnetic resonance imaging (MRI) abnormalities. We investigated age, sex, sports discipline, span from symptom onset to consultation, laterality, complication with spondylolysis, computed tomography (CT) findings, and treatment span. The average age was 14.5 years old (8-men and 5-women). The most frequent discipline was basketball. The span to consultation was 13.2 days. The number of right-side cases was 9. Seven cases were complicated by bilateral spondylolysis. MRI abnormalities were observed in all the cases. Only two patients showed abnormal findings on CT. Averagely 67 days after treatment, participants returned to their sports. Sacral alar fatigue fractures suggest that the span from onset to consultation is short. Fracture lines are often unclear on CT, and MRI is useful for diagnosis. More than half of the cases in this study were complicated by lumbar spondylolysis.